Chinese Art - Mackenzie, Finlay (Spring Books, 1968)
ronzes, pottery, porcelain, ivories, jades, sculptures and paintings -- all these mediums of the Chinese creative genius are presented in this volume in full color. On first acquaintance, Chinese art may seem a confusion of styles, shapes, supernatural figures, animals and symbols. The ancient Chinese were, in fact, an intensely realistic people who insisted on the usefulness of even the most highly developed art forms. Mr. Finlay MacKenzie has brought all his knowledge to bear in making clear to the reader the patterns of Chinese art. He has chosen the finest and most representative pieces from museums in England, America and Europe, and has provided a concise and informative introduction to each of the art forms, as well as a general historical survey of the background against which these exquisite pieces were created. -- From publisher's description.